Den kroppsliga läsningen - Joakim Sigvardson (Educare)
This paper illuminates what fiction reading means inside and outside of Swedish schools. It also argues for the need to formulate this endeavour as both an epistemological project and a phenomenological one.  At the core of this paper lies a troubling state of affairs—that reading is declining—and a wish to trace the origins of this decline to find available means for remedy. To be able to grasp what fiction reading means in a phenomenological sense, the paper first embarks on a critical discussion of the reader and the text, which is followed by a methodological and theoretical section fully devoted to the effort of describing reading as such through Michel Henry’s concept of flesh. Armed with a phenomenological understanding of the significance of reading, the paper then places fiction reading within the context of Swedish education. The phenomenological analysis finds that in education, when reading fails to be preciselyreading (pathetic-esthetic reading), it is instead often transformed into something other (objectified reading or instrumental reading) than what it sets out to be. The paper uses a literary example to concretize its findings.